A Bayesian analysis of the accumulated count of ozone exceedances in Mexico City - Achcar, Jorge A.; Rodrigues, Eliane R.; Souza, Aparecida D.P. [UNESP] (My University, 2012)
We consider the problem of understanding the behaviour of the mean number of times that a given environmental threshold is surpassed by a pollutant's concentration. We assume three parametric forms for that mean. All of them are, in one way or another, related to the mean of a non-homogeneous Poisson process. The parameters of the models will be estimated under a Bayesian point of view via Markov chain Monte Carlo (MCMC) methods. Results are applied to the daily maximum ozone measurements from the monitoring network of Mexico City. © 2013 Nova Science Publishers, Inc. All rights reserved.